(3GdJMcje aj efGRYGJ GdMhGOK GdHMQjI (B/s - (3Wg, CejQ eMeO eMehOs ((3GdEScfOQjI (B[(3eUQ(B] :s (3OGQ GdLGeYI GdLOjOI,s, 2017)
(3jJfGhd cJGH (B((3GdJMcje aj efGRYGJ GdMhGOK GdHMQj(B) (3hGdPj bGe HJCdjag (B((3CejQ eMeO eMehO Wg(B) (3aj MhGdj (B(429) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdbGfhf GdOhdj GdHMQj hGdMhGOK GdHMQjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3hbO JNjQfG aj efgLfG ddHMK GdCSdhH GdJMdjdj eSJYjfjf aj Pdc CjVG HGdCSdhH GdGSJbQGFj hGdGSJfHGWj hGdJWHjbj hjbSe ehVhY GdQSGdI ceG jdj (B: (3GdHGH GdChd (B: (3GdefGRYGJ GdfGTFI Yf GdMhGOK GdHMQjI, GdHGH GdKGfj (B: (3bVGA GdJMcje hGdefGRYGJ GdfGTFI Yf GdMhGOK GdHMQjI(B.s
(3HHdjhLQGajI (B: (3UaMI (B410-422.s
Keywords: (3GdJMcje GdOhdjs; (3GdbGfhf GdOhdj GdHMQjs; (3GdMhGOK GdHMQjI (B((3bGfhf Ohdj(B)s